Vernonia cinerea Less. supplementation and strenuous exercise reduce smoking rate: relation to oxidative stress status and beta-endorphin release in active smokers - Yankai Araya; Sriboonreung Thanyaluck; Pothongsunun Prapas; Pratanaphon Sainatee; Leelarungrayub Donrawee; Bloomer Richard J (Taylor & Francis Group, 2010)
Abstract Purpose The aim of this study was to evaluate the effects of Vernonia cinerea Less. (VC) supplementation and exercise on oxidative stress biomarkers, beta-endorphin release, and the rate of cigarette smoking. Methods Volunteer smokers were randomly divided into four groups: group 1: VC supplement; group 2: exercise with VC supplement; group 3: exercise; and group 4: control. VC was prepared by wash and dry techniques and taken orally before smoking, matching the frequency of strenuous exercise (three times weekly). Before and after a two month period, exhaled carbon monoxide (CO), blood oxidative stress (malondialdehyde [MDA], nitric oxide [NOx], protein hydroperoxide [PrOOH] and total antioxidant capacity [TAC]), beta-endorphin and smoking rate were measured, and statistically analyzed. Results In Group 1, MDA, PrOOH, and NOx significantly decreased, whereas TAC increased (p < 0.05). In Group 2, MDA and PrOOH decreased (p < 0.05), with no other changes noted (p > 0.05). In Group 3, MDA, PrOOH, NOx, TAC, and beta-endorphin levels increased significantly (p < 0.05). Group 4 showed no change in oxidative stress variables or beta-endorphine levels (p > 0.05). All groups had lower levels of CO after the intervention. The smoking rate for light cigarette decreased in group 2(62.7%), 1(59.52%), 3 (53.57%) and 4(14.04%), whereas in self-rolled cigarettes it decreased in group 1 (54.47%), 3 (42.30%), 2 (40%) and 4 (9.2%). Conclusion Supplementation with Vernonia cinerea Less and exercise provided benefit related to reduced smoking rate, which may be related to oxidaive stress and beta-endorphine levels.